"Contradictions, clashes, cominglings": The Syncretic Literacy Projects of Young Bilinguals. (19th August 2013) - Volk, Dinah
<x xml:space="preserve">Abstract</x> This article explores the concept of syncretism, its history, related concepts, and potential as a research tool. It proposes a critical syncretism for analyzing the syncretic literacy projects of three young Puerto Rican bilinguals with attention to their agency and creativity drawing on diverse languages and literacies and transforming them at home with family members' support. The projects are also analyzed within the sociohistorical contexts of the families. Challenges for research and education are discussed.